A Qualitative Assessment of Clinical Practice Guidelines and Patterns for Congenital Cytomegalovirus in the United States - Stephanie Kalb; John Diaz-Decaro; Harout Tossonian; Andrew Natenshon; Lori Panther; James Mansi; Laura Gibson (MDPI AG, 2023)
Cytomegalovirus (CMV) infection during pregnancy may result in long-term health problems for children with congenital CMV (cCMV). Currently, no prevention or treatment interventions are approved by the Food and Drug Administration for a cCMV indication. Healthcare provider and public awareness is low, and formal clinical practice guidelines and local practice patterns vary. A pilot study of eight cCMV experts was performed using qualitative semi-structured interviews to better understand clinical practice guidelines and patterns in the United States. Results from participant interviews highlighted the need for better prenatal diagnostic techniques, broader neonatal screening opportunities, and more robust evidence supporting intervention strategies. Healthcare provider and public partnerships are essential for advancing cCMV guidelines and improving care delivery. Our results provide a preliminary knowledge base and framework for developing a consensus cCMV research agenda to address evidence gaps that limit the revision of clinical practice guidelines. The changes in clinical practice patterns that may arise as a result of further research have the potential to reduce risk during pregnancy and improve care for children with cCMV infection.